A maternal hypoxia mouse model to study the effect of late gestational hypoxia on offspring lung outcomes - Nguyen, Thi-Tina N.; Lewis, Caitlin V.; Hidalgo, Daniel Colon; Posey, Janelle N.; Jordan, Mariah; Porfilio, Timothy E.; Grayck, Maya R.; Wright, Clyde J.; Delaney, Cassidy; Nozik, Eva S. (Frontiers in Physiology, 2025)
Extremely preterm birth predisposes infants to bronchopulmonary dysplasia and associated pulmonary hypertension (PH). High altitude exposure during pregnancy has also been shown to worsen infant lung and pulmonary vascular outcomes. Animal models addressing the mechanisms for how maternal hypoxia impacts postnatal and adult lung and pulmonary vascular outcomes are lacking and development of a model to address this gap would enable new mechanistic studies. We hypothesize that late gestational hypoxia disrupts lung and pulmonary vascular development in the offspring, leading to abrupted lung development and PH in adulthood. Pregnant wild-type mice were exposed to hypobaric hypoxia at 505 mmHg, from day 16.5 of gestation until birth. Lung and pulmonary vascular outcomes were measured in juvenile and mature offspring. We found that late gestational hypoxia resulted in abrupted alveolar and pulmonary vascular development in juvenile offspring and that adult offspring showed persistent abrupted alveolar development as well as PH. This striking model will provide a new opportunity to determine mechanisms responsible for poor outcomes secondary to maternal hypoxia and assess important factors that increase susceptibility to adult diseases in former preterm infants.